Modeling gamma detectors in OpenMC: validation of a newly implemented pulse-height tally - Fichtlscherer, Christopher; Miah, Milon; Frieß, Friederike; Göttsche, Malte; Kütt, Moritz (Progress in nuclear energy, 2024)
Gamma spectroscopy measurements can be simulated using a pulse-height tally functionality of Monte Carlo particle transport codes. Such a functionality must account for the complete simulation history of a particle’s energy deposited in a particular volume. OpenMC, an open-source application for neutron and photon particle transport which is widely used in the nuclear engineering community, previously lacked adequate simulation capabilities for gamma spectroscopy. In this paper, we outline the implementation of the photon pulse-height tally for OpenMC. Additionally, we validate the new function by comparing results to analytical calculations, other software, and experimental data.
Gesehen am 18.10.2024